Effect of African Leaves Extract (Vernonia amygdalina DEL.) on Wound Healing Velocity after Tooth Extraction in Rattus norvegicus - Andre Kusuma Ruslim; Silvia Anitasari; Sjarif Ismail; Eka Marwansyah Oli’I; Sinar Yani (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2017)
Povidone iodine is an antiseptic that is often used for wounds after tooth extraction, but is often debated because it can cause damage to cells and tissues. African leaf (Vernonia amygdalina Del.) from the family Asteraceae has saponins as anti-microbial, anti-inflammatory and antioxidant flavonoids as that all may be able to accelerate wound healing. To investigate the activity of extracts of Vernonia amygdalina folia (VAF) to accelerate the process of wound healing after tooth extraction in rats. VAF extracted by maceration using methanol. Wistar male rats as much as 6 groups (n = 5 mice each group) performed tooth extractions, and then observed the reduction of gingival socket closure for 21 days after being given povidone iodine, distilled water and methanol extract group VAF by 4 concentration. The closure of the wound after tooth extraction in the group of povidone iodine rats occurred on the 8th day, the group aquadest cover the wound occurred on the 12th day, the extract group 1, 3, 5, 7% sequentially occur wound closure on day 6th, 5th, 4th and 4th. VAF methanol extract of the leaves can accelerate wound healing after tooth extraction of mice